Addressing the water-energy nexus: A focus on the barriers and potentials of harnessing wastewater treatment processes for biogas production in Sub Saharan Africa. Issue 5 (May 2022) - Ijoma, Grace N.; Mutungwazi, Asheal; Mannie, Thulani; Nurmahomed, Weiz; Matambo, Tonderayi S.; Hildebrandt, Diane
Abstract: Several anthropogenic activities reduce the supply of freshwater to living organisms in all ecological systems, particularly the human population. Organic matter in derived wastewater can be converted into potential energy, such as biogas (methane), through microbial transformation during anaerobic digestion (AD). To address the current lack of data and values for wastewater generation in Sub-Saharan Africa, this review analyzes and estimates (at 50% and 90% conversion rates) the potential amount of wastewater-related sludge that can be generated from domestic freshwater withdrawals using the most recent update in 2017 from the World Bank repository and database on freshwater status in Sub-Saharan Africa. The Democratic Republic of the Congo (DRC) could potentially produce the highest estimate of biogas in Sub-Saharan Africa from domestic wastewater sludge of approximately 90 billion m 3, which could be converted to 178 million MWh of electricity annually, based on this extrapolation at 50% conversion rates. Using same conversion rates estimates, at least nine other countries, including Guinea, Liberia, Nigeria, Sierra Leone, Angola, Cameroon, Central African Republic, Gabon, and Congo Republic, could potentially produce biogas in the range of 1–20 billion m 3 . These estimates show how much energy could be extracted from wastewater treatment plants in Sub-Saharan Africa. AD process to produce biogas and energy harvesting are essential supplementary operations for Sub-Saharan African wastewater treatment plants. This approach could potentially solve the problem of data scarcity because these values for Freshwater withdrawals are readily available in the database could be used for estimation and projections towards infrastructure development and energy production planning. The review also highlights the possibilities for energy generation from wastewater treatment facilities towards wastewater management, clean energy, water, and sanitation sustainability, demonstrating the interconnections and actualization of the various related UN Sustainable Development Goals. Abstract : Sustainability; Anaerobic digestion; Clean energy; Waste-to-energy; Circular economy.